Aegyptiaca : a catalogue of Egyptian objects in the Aegean area - Pendlebury, J. D. S. 1904-1941. (Cambridge University Press, 2014)
First published in 1930, this book collects all of the ancient Egyptian objects dating from before the Twenty Seventh Dynasty that were known to have been found at Greek archaeological sites prior to original publication. The book groups the items by find site, and photographs of many of the objects are included at the end of the text.